(untitled) (REGE Revista de Gestão, 2021)
AbstractPurpose – The purpose of this article is to contribute to studies on organizational ambidexterity by analyzinghow an incumbent company is managing its innovation structures and balancing exploitation and explorationactivities to generate value in a digital economy context.Design/methodology/approach – The research was designed in a qualitative format through a single casestudy in a Brazilian financial institution, with semi-structured interviews conducted with internal and externalplayers.Findings – Based on the case study, two possible contributions emerged as results, to fill the research gap: theneed to develop more complex innovation structures, which act in a way that is integrated to the ecosystem; andthe establishment of an organizational function, with a specific mandate to seek innovation in new businessplatforms.Originality/value – Although the theory gives evidence about the potential that ambidexterity represents forcompanies, ‘how’ to orchestrate the trade-offs to achieve it is not clear, particularly in regards to first stepstoward ambidexterity. This work aims to contribute to fill this gap through an empirical study in a largeBrazilian company, analyzing its trajectory toward ambidexterity.